A Dual-Linearly-Polarized Center-Fed Quadrifilar Helix Antenna Loaded With Reverse Helices - Xunting Yang; Yifeng Xu; Yuhang Dou; Miao Zhang (IEEE Access)
This paper proposes a dual-linearly-polarized (DLP) center-fed quadrifilar helix antenna (CF-QHA) loaded with reverse helices. It features a small transverse area, hollow-core structure, enhanced bandwidth, high cross-polarization discrimination (XPD), and high gain. The proposed antenna comprises two pairs of diagonal helical arms along ±45° directions. By changing the feeding point to the center of each helical arm, the center feed mechanism is introduced first to improve the impedance matching, compared with the previous end-fed DLP-QHA. Loading reverse helices with the CF-QHA in parallel further enhances the XPD performance. In addition, each pair of diagonal helical arms employs a differential feed to ensure LP radiations and high isolation. For demonstration, a prototype is fabricated and tested. According to the measured results, the 10-dB return loss bandwidths of the proposed ±45° DLP CF-QHA respectively range over $2.13-2.68$ GHz (22.87%) and $2.1-2.69$ GHz (24.63%), where XPDs higher than 21 dB and isolation better than 24 dB are achieved. The DLP CF-QHA is expected to provide the industry with more design options in base station applications.